2006
DOI: 10.1158/1055-9965.epi-05-0959
|View full text |Cite
|
Sign up to set email alerts
|

A Role for XRCC4 in Age at Diagnosis and Breast Cancer Risk

Abstract: Genetic variants in DNA repair genes influence the ability to repair damaged DNA. Unrepaired or improperly repaired DNA may lead to genetic instability and carcinogenesis. We evaluated the role of four tagging single nucleotide polymorphisms (tSNP) in the DNA repair gene, XRCC4, and its association with breast cancer risk and age at diagnosis of breast cancer in 464 cases and 576 controls selected to be BRCA1/2 mutation negative from high-risk Utah pedigrees. We observed a significant association for two 4-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…To date, GWAS conducted for BC have identified more than 80 breast cancer susceptibility loci (all summarized in [ 3 ]). Although, several candidate gene association studies for BC have been conducted during the last decade [ 4 10 ], many of them were underpowered due to small sample size, resulting in inconsistent and not reproducible findings [ 11 , 12 ]. To date, only one polymorphism located in the coding region of CASP8 (rs1045485) has shown promise as a breast cancer predisposition risk factor [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, GWAS conducted for BC have identified more than 80 breast cancer susceptibility loci (all summarized in [ 3 ]). Although, several candidate gene association studies for BC have been conducted during the last decade [ 4 10 ], many of them were underpowered due to small sample size, resulting in inconsistent and not reproducible findings [ 11 , 12 ]. To date, only one polymorphism located in the coding region of CASP8 (rs1045485) has shown promise as a breast cancer predisposition risk factor [ 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large studies on the role of XRCC4 single-nucleotide polymorphisms (SNPs) in cancer susceptibility have been performed in hepatocellular carcinoma [ 17 ], lung cancer [ 18 ], multiple myeloma [ 19 ], and oral cancer [ 20 ]. Notably, there have only been a few studies on the associations between genetic variants of XRCC4 and breast cancer susceptibility; these studies were performed regardless of the BRCA1/2 status, and the results were inconclusive [ 21 - 23 ]. Furthermore, the biological underpinnings of these genetic associations have not yet been well established.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Taiwan among Asian women found that carrying an increasing number of variant alleles in XRCC4 was associated with higher disease risk [8]. Another study found associations of XRCC4 haplotypes with age at diagnosis of BC and risk in non-BRCA1/2 heritable individuals [16]. In the current study, we examined six SNPs in XRCC4.…”
Section: Discussionmentioning
confidence: 99%